Quantitative Evaluation of Hormesis in Breast Cancer Using Histoculture Drug Response Assay - Yuka Aoishi; Tatsuya Yoshimasu; Shoji Oura; Mitsumasa Kawago; Yoshimitsu Hirai; Miwako Miyasaka; Takuya Ohashi; Yoshiharu Nishimura (Dose-Response, 2019)
Purpose: Hormesis is a phenomenon of growth stimulation at low doses and inhibition at higher doses. In cancer treatment, little is known about how hormesis affects cancer cell proliferation. We evaluated the hormetic dose–response relationship of paclitaxel using surgically resected breast cancer specimens on the basis of histoculture drug response assay (HDRA). Methods: We used surgically resected fresh tumor specimens from 22 patients with breast cancer: 17 invasive ductal, 3 mucinous, and 2 other “special-type” cancers. All patients were female, ranging in age between 40 and 86 (median 60) years. Small pieces of viable cancer tissue were placed on collagen gel and cultured for 7 days with paclitaxel. Inhibition rates of paclitaxel at several concentrations were measured and fitted to a sigmoid dose–response curve. Results: Hormesis was observed in 9 of the 22 cases; ED 50 of cytotoxic effect was significantly higher ( P = .0036) in hormesis (H) group (44.6 ± 4.2 µg/mL) than in nonhormesis (N) group (26.7 ± 3.5 μg/mL). Conclusion: We evaluated hormesis in breast cancer tissue using HDRA for the first time although previously confirmed in cultured cells. Hormesis seems to occur in patients undergoing treatment with anticancer agents, especially in a metastatic setting. Meanwhile, tumor growth may be stimulated in patients who are resistant to paclitaxel.